Clinic information system / Miftah Arfan Said - Miftah , Arfan Said (2003)
This project can be defined as an open system, which attempts to integrate and communicate the outside and inside flow of information in hospitals and provide the functions common for all applications. The wed-based Clinics information System allows users, using any web browser but best view with Internet Explorer and Netscape Communicator, to search for health treatment, and on the other hand lets the authorized health treatment provider to update patients, medical data. The rationale behind this development is to eliminate the difficulties faced when trying to search through conventional channel such as calling up hospitals or clinics, and flipping through yellow pages. Waterfall model approach was selected for the development process because it support rapid application development and reduces the risks involved. Software engineering and system analysis principles based on this methodology were applied throughout the development phases: system analysis, design, coding, testing, and implementation. The development tools selected for this project were Microsoft Visual InterDev 6.0 along side with Microsoft Paint; whereas the back-end database used was Microsoft Access with Active Server Page as the web server. Both server deployed on Window XP server platform.